Surgical nuances in the management of pineal region tumors via the occipital transtentorial approach without using brain retractor - Lingmin Shao; Mohammad Rohul Amin; Jia Liu; Renzhong Liu; Zhihong Jian (Interdisciplinary Neurosurgery)
Objective: Access to the pineal region has always represented a formidable challenge to the neurosurgeons. This study aims to explore the surgical techniques of the occipital transtentorial approach (OTA) without using brain retractor for excision of pineal region tumors based on the author’s experience and literature review. Methods: A retrospective analysis was performed of patients who underwent surgery for pineal tumors via OTA using dynamic retraction at our institution from 2018 to 2022. The clinical data, surgical procedure, and results were examined. Results: Twelve patients underwent surgery via OTA for treatment of pineal tumors. In all cases, it was feasible to complete surgery without using brain retractor. Gross total resection was achieved in 10 cases (83.3 %), while subtotal resection in 2 cases (16.7 %). There were no mortalities. Three patients presented with upper gaze palsy after surgery, 2 of them experienced complete recovery at the third month follow-up. Only one patient had residual neurologic deficit. Two patients reported transit diplopia after surgery. No postoperative hemianopsia was observed in this series. Conclusion: The occipital transtentorial approach is effective for the removal of tumors in the pineal region. Dynamic retraction with handheld instruments and meticulous dissection of arachnoid membrane around the deep veins can provide a sufficient working space.